The Effect of Company Size and Liquidity on Company Value With Capital Structure as An Intervening Variable Empirical Study on The Indonesia Stock - Masyaili Masyaili (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This study examines and determines the effect of firm size and liquidity on firm value with capital structure as the intervening variable. This study took a sample of companies members of the LQ 45 index listed on the Indonesia Stock Exchange. The type of data used in this study is secondary data in the form of the company's annual financial reports for the LQ 45 Index for the 2018-2021 period. The population in this study is 45 companies that are members of the LQ45 index. The sampling method used in this study was purposive sampling, namely a sampling method with certain criteria so that only 35 companies met the requirements. Data were analyzed using path analysis. The results of the study are as follows: (1) Company size has a positive and not significant effect on capital structure, (2) liquidity has a positive and significant effect on Capital Structure, (3) company size has a positive and not significant effect on firm value, (4) liquidity has an effect positive and not significant to firm value, (5) capital structure has a positive and significant effect on firm value, (6) capital structure does not significantly mediate the effect of firm size on firm value, (7) capital structure does not significantly mediate the effect of liquidity on firm value.